RESEÑA de : Rodríguez Huéscar, Antonio. José Ortega y Gasset’s metaphysical innovation : a critique and overcoming of idealism. New York : State University of New York Press, 1995 - Hermida Lazcano, Pablo (Investigaciones Fenomenológicas, 1995)
-